Comparison of Hydroxypropyl Methylcellulose and Alginate Gel Films with Meloxicam as Fast Orodispersible Drug Delivery - Barbara Jadach; Martyna Misek; Jan Ferlak (Gels, 2023)
The aim of the study was the preparation and comparison of two types of orodispersible gel films (ODF) by the solvent casting method. Natural polymers: sodium alginate (ALG) or hydroxypropyl methylcellulose (HPMC) were used as the gel film formers, and Kollidon or microcrystalline cellulose was used as the disintegrant. Meloxicam (MLX), the drug used to treat rheumatic diseases for children and adults, was proposed as the active pharmaceutical ingredient (API). The influence of the polymer and disintegrant on the properties of ODF was investigated. The evaluation of prepared gel films was based on appearance description, mass uniformity measurement, disintegration time, API content, film wettability, and water content. Also, the dissolution test was prepared in a basket apparatus using artificial salvia (pH = 6.8) as the medium. The obtained API release profiles were analyzed for the similarity factors (f2) with the DDSolver software. The results showed that independently of the polymer or disintegrant, using the solvent casting method, gel films have a similar appearance and active substance content close to the theoretical value and water content of less than 10%. Only the type of polymer influences the release profiles of MLX. However, the disintegration time was longer than 30 s, which makes the films non-fast-dissolving drug delivery systems. This means that for the ODF system, further evaluation is required, and some changes in the composition of the film have to be done.